Crystal structure of 5-(1, 3-dithian-2-yl)2H-1, 3-benzodioxole. (March 2015) - Zukerman-Schpector, Julio; Caracelli, Ignez; Stefani, Helio A.; Gozhina, Olga; Tiekink, Edward R. T.
No abstract available